Taurodeoxycholic acid alleviates diquat-induced intestinal barrier function injury in mice through the upregulation of Nrf2-mediated signaling pathway - Jinglei Liu; Yuhan Zhang; Mengzhen Song; Xuming Guo; Jinping Fan; Shiyu Tao (BMC, 2024)
Abstract Oxidative stress is an important contributor to gastrointestinal diseases in multiple ways. Taurodeoxycholic acid (TDCA) is a metabolite of bile acids and has anti-inflammatory and protective effects on the intestinal tract. However, whether TDCA can alleviate oxidative stress in the intestine is still unclear. Here, we investigated the effects of TDCA on diquat-induced oxidative stress in the jejunum and its mechanism. The results revealed that TDCA increased the concentrations of antioxidant enzymes in the serum, jejunal tissue and intestinal epithelial cells of the mice, as did the expression of tight junction-associated proteins and the Nrf2 protein in the jejunal epithelial tissue and intestinal epithelial cells. We then explored the mechanism of Nrf2 with ML385 (a specific Nrf2 inhibitor). The results showed that after ML385 treatment, the levels of antioxidant enzymes were significantly decreased in the serum, jejunum, and intestinal epithelial tissues of the mice. The expression of tight junction proteins in jejunum epithelial tissues and intestinal epithelial cells was also decreased. In conclusion, our study suggests that TDCA alleviates oxidative stress to improve intestinal barrier function through the Nrf2-mediated signaling pathway. These findings help elucidate the role of TDCA in protecting the intestinal barrier and its mechanism of action, providing insights for the prevention and treatment of intestinal diseases caused by oxidative stress.